2007
DOI: 10.1136/jech.2006.054346
|View full text |Cite
|
Sign up to set email alerts
|

Suicide among male veterans: a prospective population-based study

Abstract: Veterans in the general US population, whether or not they are affiliated with the Department of Veterans Affairs (VA), are at an increased risk of suicide. With a projected rise in the incidence of functional impairment and psychiatric morbidity among veterans of the conflicts in Afghanistan and Iraq, clinical and community interventions that are directed towards patients in both VA and non-VA healthcare facilities are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
220
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 316 publications
(231 citation statements)
references
References 29 publications
10
220
1
Order By: Relevance
“…Prior work has identified relationships between functional decline or functional status and suicide, 34,35 and it has been noted to be predictive of suicide independent of physical illness. However, it remains unclear how functional decline relates to depression among suicide decedents; some studies show an independent association between functional status and suicide, while others suggest that mood disorders mediate this relationship.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior work has identified relationships between functional decline or functional status and suicide, 34,35 and it has been noted to be predictive of suicide independent of physical illness. However, it remains unclear how functional decline relates to depression among suicide decedents; some studies show an independent association between functional status and suicide, while others suggest that mood disorders mediate this relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Our finding that the odds of white veterans dying by suicide are approximately twice those of non-white veterans is commensurate with prior research. 35,41 Similarly, though less wellstudied, service connected disability status has been shown to be protective as well, presumably by increasing access to healthcare services by decreasing out of pocket costs. 5,42,43 We found that PTSD diagnosis was not associated with suicide.…”
Section: Discussionmentioning
confidence: 99%
“…[1] Kaplan reported a doubling of risk in US male veterans compared with non-veterans, using data from the 1986-1994 National Health Interview Survey (NHIS), [2] although Miller et al re-examined the same dataset and found only a modest non-significant increase in risk. [3] LeardMann found no increase in risk associated with military-specific variables in the US military Millennium Cohort Study 2005 and found that the overall rate of suicide was no higher than in the general population, but there was an increased risk in those aged under 25 years.…”
Section: Introductionmentioning
confidence: 99%
“…Suicide risk is elevated for those who have participated in military service, particularly for males, who are at a higher risk of suicide compared with non-Veterans in all age groups except the oldest (Kaplan, McFarland, Huguet, & Valenstein, 2012). A population-based study of pre-9/11 male Veterans also found that Veterans were at an increased risk of suicide compared with non-Veterans (Kaplan, Huguet, McFarland, & Newsom, 2007). Veterans engage in higher 5 Several DoD databases record information on battlefield injuries or medical care that is delivered in theater that would allow for a study of the type of care that is needed for patients who would not have survived their injuries in previous conflicts.…”
Section: Prevalence Of Rare Health Conditions and Other Risks Among Vmentioning
confidence: 95%